Living in the riverbanks: Case of the Ogan malay community settlement, South Sumatera (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This article attempts to understand how the settlement layout of riverbank communities, with the case in the Ogan Malay community in South Sumatra province. This article is based on empirical reality in which the community tends to always live on the riverbank, especially the riverbank, with raging water. For the Ogan Malay community, the settlement is an area consisting of villages as dwellings, but also include agricultural areas (fields, fields, and gardens) and other supporting areas, as a source of life. As a riverbank community, the river has always been central in determining the layout of elements of its settlements, thus creating a unique settlement layout pattern. This article is the result of ethnographic (anthropological) research conducted by the author in April - June 2019. Data were collected through depth interviews with indigenous leaders and local communities in the location, as well as through participant observation of life activities in the research field. The results showed that living on the riverbanks is not arbitrary, but based on the community's knowledge system on the river environment itself. This knowledge creates a unique pattern of community settlement layout, where the river has always been central in the preparation of layout planning.
Keywords: Villages; Riverbank; Pattern of Settlement; Ogan Malay; South Sumatera.